"Actual experience": correcting misconceptions through analyzing Harriet Wilson's Our Nig - Fejer, Azhar Noori; Talif, Rosli (David Publishing Company, 2014)
African-American writers during the 19th century wrote in the shadow of the prominent romance, sentimental, and domestic fiction. Harriet Wilson’s Our Nig (1859) reflects an “alternative social character”, for the female protagonist suffers racism in the free North, because she is a mulatto child. Through depicting the life of free blacks, who supposedly lives a better life than Southern slaves, Wilson exposes how she has actually lived and sensed life in antebellum America. According to Raymond Williams (2011), there are two kinds of literary writings. The first represents the general tendency of the age, and he calls it “dominant social character”; representing the majority content of both the public writing and speaking. But, another different literary writing lives in its shadow; one that usually leads the conflicts of the time. It is the “alternative social character”; the literature of the victims of repression and marginalization, produced by the lower class, women, and blacks. They reflected how they were dehumanized, and exposed their suffering and abasement. They also aimed to prove individualism. The novel reveals how racism in the North could be worse than the slavery of the South. This paper shows Wilson deviation from the “her brethren” in writing her novel. It unveils significant truths concerning black women’s status in antebellum America. It discusses how the author attempts to correct certain misconceptions through her female character.